ANALISIS PENGARUH RASIO KEUANGAN TERHADAP FINANCIAL DISTRESS - Febrianti, Luthfia; Tumirin (SUSTAINABLE, 2024)
This study aims to examine the effect of financial ratios on financial distress. This type of research is quantitative research. The population in this study were Industrial Sector Companies Listed on the Indonesia Stock Exchange. Then, the sample obtained in this study was 102 companies using a purposive sampling method. The data used in this study are secondary data through www.idx.co.id. The analysis method used is logistic regression analysis using the SPSS program. The results of this study indicate that the liquidity ratio (CR) has no effect on financial distress; solvency ratio (DER) effect financial distress; profitability ratio (ROA) has no effect on financial distress; growth ratio affects financial distress; activity ratio affects financial distress.